Implementation of a GAP label in a differentiated-product industry: a welfare evaluation with a random coefficients model for Mar del Plata, Argentina - Lacaze, María Victoria (2012)
This paper evaluates the effect on market shares and consumer surplus of the introduction of a Good Agricultural Practices (GAP)-labeled product in the frozen fried potatoes (FFP) industry. We first estimate a model of household demand in Mar del Plata, Argentina, using scanner data and demographic information. We find that higher income individuals are more concerned about health and nutrition, and that younger and lower-income consumers are more price-sensitive. Then we postulate that a properly GAP-labeled FFP is available in the market, and we assess its effect by using the estimated utility function and prior information about consumers' declared willingness to pay (WTP) for sustainably produced potatoes. We find that the older the individual, the greater the influence of the hypothetical introduction of the GAP-labeled product; the relationship is less conclusive in the case of income. Finally, we predict the results of a greater consumer surplus extraction by fixing a higher price for the new product, and we calculate the maximum increase in the marginal cost that the firm would be able to afford if farmers charge higher prices for GAP fresh potatoes.